Pulseless Electrical Activity: Echocardiographic Explanation of a Perplexing Phenomenon - David C. Parish; Hemant Goyal; Hemant Goyal; Erskine James; Francis C. Dane (Frontiers in Cardiovascular Medicine, 2021)
Pulseless electrical activity (PEA) is considered an enigmatic phenomenon in resuscitation research and practice. Finding individuals with no consciousness or pulse but with continued electrocardiographic (EKG) complexes obviously raises the question of how they got there. The development of monitors that can display the underlying rhythm has allowed us to differentiate between VF, asystole, and PEA. Lack of clear understanding of the emergence of PEA has limited the research and development of interventions that might improve the low rates of survival typically associated with PEA. Over 30 years of studying and practicing resuscitation have allowed the authors to see a substantial rise in PEA with variable survival rates, based on the patients' illness spectrum and intensity of monitoring. This paper presents a small case series of individuals with brain death whose family members consented to the echocardiographic observation of the dying process after disconnection from life support. The observation from these cases confirms that PEA is a late phase in the clinical dying process. Echocardiographic images delineate the stages of pseudo-PEA with ineffective contractions, PEA, and then asystole. The process is contiuous with none of the sudden phase shifts seen in dysrhythmic events such as VF, VT or SVT. The implications of these findings are that PEA is a common manifestation of tissue hypoxia and metabolic substrate depletion. Our findings offer prospects for studies of the development of interventions to improve PEA survival.